2004
DOI: 10.1016/j.trstmh.2004.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Is praziquantel therapy safe during pregnancy?

Abstract: Schistosomiasis control programmes are generally based on mass distribution of praziquantel (PZQ). This approach has been further strengthened by studies that demonstrated reduction in schistosomiasis-related morbidity following regular use of PZQ. Many women were excluded from this therapy when pregnant. Since a high degree of parity is achieved in many schistosomiasis-endemic regions, excluded women often miss treatment and consequently the beneficial effect of this therapy. This study investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Based on previous observations [15], a cross-sectional study was conducted between August 1 and September 30, 2010, at a prenatal care clinic at Araba Waeshreen Hospital, Geizera, Sudan. Pregnant women attending prenatal care for the first time were invited to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous observations [15], a cross-sectional study was conducted between August 1 and September 30, 2010, at a prenatal care clinic at Araba Waeshreen Hospital, Geizera, Sudan. Pregnant women attending prenatal care for the first time were invited to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Although data on the epidemiology of schistosomiasis during pregnancy are available for other African countries [10,13,14], no published data exist for Sudan. The present study was carried out as part of the surveys conducted by the Sudan Ministry of Health and the University of Khartoum to provide data necessary for required interventions and to add to previous research on schistosomiasis among pregnant women [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A desensitization procedure was performed in a patient with paragonimiasis using small to increasing doses (30, 60, 100, 150, 300, 600, and 1,200 mg) of praziquantel at 90 min intervals, and the patient was then successfully treated with the standard dose of praziquantel (75 mg/kg daily for 3 consecutive days) [7]. In pregnant women, praziquantel treatment at a single dose of 40 mg/kg was found effective and safe for treatment of S. mansoni infection [80, 81]. …”
Section: New Trials and Problems To Be Solvedmentioning
confidence: 99%
“…In marine models and two observational studies in humans, Schistosoma infection during pregnancy was associated with reduced birth weight, although a recent treatment trial in Schistosoma mansoni did not detect this association. Adam et al (2004) reported that there were no significant differences between the group which received PZQ during pregnancy compared with which had not received the drug during pregnancy in the rate of abortion or preterm deliveries. No congenital abnormalities were noted by clinical examination in any of the babies born to either group.…”
Section: Discussionmentioning
confidence: 99%